2023
DOI: 10.3390/polym15071614
|View full text |Cite
|
Sign up to set email alerts
|

Energy Absorption and Ballistic Performance of Epoxy Composite Reinforced with Arapaima Scales

Abstract: Arapaima scales possess a hierarchical structure capable of absorbing a considerable amount of energy before fracture. These natural dermal armors present significant potential in the sustainable development of cost-effective composites. This work aimed, for the first time, to analyze the impact resistance and ballistic performance of arapaima scale-reinforced epoxy composites and their potential application in multilayered armor systems (MAS). Composite plates were prepared with 20%, 30%, and 40 vol% of arapa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…On the other hand, composites reinforced with guaruman fibers [78], hemp fibers [25], and arapaima scales [76] exhibited inferior ballistic performance when compared to epoxy/ubim composites.…”
Section: Ballistic Testsmentioning
confidence: 99%
“…On the other hand, composites reinforced with guaruman fibers [78], hemp fibers [25], and arapaima scales [76] exhibited inferior ballistic performance when compared to epoxy/ubim composites.…”
Section: Ballistic Testsmentioning
confidence: 99%
“…The results have shown that the difference in velocity and angle significantly affects the energy absorption capacity of the composites [48,49]. Additionally, the orientation of the fibers in the impact direction has been found to improve the impact energy absorption and overall mechanical response of the composites [50,51]. Finite element simulations have been used to evaluate the behavior of composite panels under ballistic impacts, providing insights into the number of layers broken, delamination effects, and deformation patterns [20].…”
Section: Energy Absorptionmentioning
confidence: 99%